Consumer perceptions of influencer gifting - André Marchand; Andrea Holler; Theresa Dünschede (Psychology & Marketing, 2024)
Many social media influencers promote products they receive from brands, which send those items without any explicit obligations but with the objective of being endorsed voluntarily. With increasing frequency, brands send their products together with additional gifts that influencers can, but do not have to, display either. For example, a branded perfume might be complemented by additional gifts of flowers, champagne, and macarons. Through such elaborate influencer gifting, brands hope to elicit more favorable reactions from both influencers and consumers. However, elaborate influencer gifting also raises concerns about consumer perceptions. With four experiments, this research shows that influencer gifting is superior to paid influencer marketing in terms of influencer trustworthiness and brand attitude outcomes, which can be explained by the increased effort signaled in the business relationship between the brand and the influencer. However, elaborate gifting also can prompt stronger perceptions of a persuasive attempt by the brand, which can lead to decreased trust in influencers who display the elaborate gifts voluntarily. The negative effect linked to perceptions of a persuasive attempt can be mitigated if the elaborate gift is justified by a brand occasion, such as the brand's anniversary.
Keywords: 650; business gifts; influencer marketing; persuasion knowledge; relationship investment